Histology Altering Effect of Smoking in Rodents’ Trachea - Shakeela Nazir, Fatima Qaiser, Ashiq Hussain, Asma Kazi, Aisha Aziz, Rafaqat Shafique (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The purpose of this study was to investigate the effects of the cigarette smoke. Duration & Place of Study: Jan 2018 to may 2021 Rashid Latif medical college Lahore Material and Method: Two different groups of male albino rats were exposed to cigarette smoke using a specially developed smoking machine for duration of three months on a daily basis over the course of the experiment. Both populations of rats were made up entirely of albinos. Result: Significant histological abnormalities occurred in the tracheal epithelium of albino rats that were exposed to cigarette smoke for a period of three months. The rats were given the smoke. The multiplication of epithelial cells, the disruption of the cilia, and the formation of inclusion bodies were some of the alterations that occurred as a result of this. In addition to alveoli that had collapsed and blood extravasations, a considerable thickening of the alveolar wall of the lung alveoli was seen. Conclusion: These modifications show that nicotine may generate changes in tissue that are comparable to those induced by chronic irritation of tissue. This may result in a reduction in the efficiency of gaseous exchange in alveoli and may predispose to the development of neoplastic abnormalities.